Interactions between human BRCA2 protein and the meiosis-specific recombinase DMC1 - Thorslund, Tina (Nature Publishing Group, 2007)
Germline mutations in BRCA2 predispose to hereditary breast cancers. BRCA2 protein regulates recombinational repair by interaction with RAD51 via a series of degenerate BRC repeat motifs encoded by exon 11 (BRCA2(996–2113)), and an unrelated C-terminal domain (BRCA2(3265–3330)). BRCA2 is also required for meiotic recombination. Here, we show that human BRCA2 binds the meiosis-specific recombinase DMC1 and define the primary DMC1 interaction site to a 26 amino-acid region (BRCA2(2386–2411)). This region is highly conserved in BRCA2 proteins from a variety of mammalian species, but is absent in BRCA2 from Arabidopsis thaliana, Caenorhabditis elegans, and other eukaryotes. We demonstrate the critical importance of Phe2406, Pro2408, and Pro2409 at the conserved motif (2404)KVFVPPFK(2411). This interaction domain, defined as the PhePP motif, promotes specific interactions between BRCA2 and DMC1, but not with RAD51. Thus, the RAD51 and DMC1 interaction domains on BRCA2 are distinct from each other, allowing coordinated interactions of the two recombinases with BRCA2 at meiosis. These results lead us to suggest that BRCA2 is a universal regulator of RAD51/DMC1 recombinase actions.